Practical Industrial Internet of Things security : a practitioner's guide to securing connected industries - Bhattacharjee, Sravani (Packt Publishing, 2018)
This book provides you with a comprehensive understanding of Industrial IoT security; and practical methodologies to implement safe, resilient cyber-physical systems. It will help you develop a strong foundation and deeper insights on the entire gamut of securing connected industries, from the edge to the cloud.